THE ROLE OF DIGITAL LEARNING TOOLS IN IMPROVING LITERACY SKILLS: A SYSTEMATIC REVIEW OF THE LITERATURE - Loso Judijanto; Rusiadi (Adisam Publisher, 2025)
This research examines the role of digital learning tools in improving literacy skills through a systematic review of the literature. The results show that digital technologies, such as interactive learning apps, e-books and multimedia platforms, have a significant positive impact on the development of literacy skills at different levels of education. These tools offer a more engaging and interactive learning experience, increasing students' interest and comprehension in reading. In addition, the use of digital tools allows for more personalised and adaptive learning to the needs of individual students. However, the successful implementation of digital technology relies heavily on supporting qualities such as equitable access to technology, adequate teacher training, and appropriate evaluation and approaches. This research emphasises the importance of collaborative efforts from educational institutions, teaching staff, parents and the surrounding environment in maximising the potential of digital learning tools to effectively improve literacy skills.